Experimental, numerical, and analytical study of concrete beams reinforced with steel stirrups and embedded with functional plates. (May 2022) - Van Hong Bui, Linh; Thongchom, Chanachai; Sirimontree, Sayan; Nguyen, Phuoc Trong; Nguyen, Thanh-Truong; Keawsawasvong, Suraparb; Nuaklong, Peem; Jongvivatsakul, Pitcha
Highlights: Reinforced concrete (RC) beams embedded with functional plates are tested. Beams with functional plates perform better shear efficiency. Finite element analyses of plate-RC beams under critical parameters are performed. Beam behavior depends on the material and geometry variables of functional plates. A proposed model for shear strength estimation of embedded plates is rational. Abstract: This study experimentally, numerically, and analytically investigates the shear performance of reinforced concrete (RC) beams embedded with functional plates as shear and tensile reinforcement. Experiments on four RC beams including two reference specimens and two plated specimens are conducted. The beams are simulated by the finite element method (FEM) with the commercial package ANSYS. A parametric study for examining the important design variables is conducted by FEM simulation. Based on the experimental and numerical data, a new expression for the shear strength model of plate-RC beams is proposed. Results show that the embedment of the continuous functional plates enhances the performance of RC beams with respect to the load-carrying capacity, stiffness, and deformation. The FE models can predict the structural responses of the steel-plate RC beams with high accuracy. Results of the parametric studies provide new insights into the application of the functional plates for reinforcing the RC beams as partial or entire substitutes for traditional steel stirrups. The proposed shear strength model demonstrates better prediction ability than a previous formula for the shear capacity of functional-plate-RC beams.